The Utilization of Acid as a Color Stabilizer in the Extraction of Anthocyanins from the Lakum (Cayratia trifolia L.) Peel - Aryo E. Peluru; Paulus H. Abram (Jurnal Akademika Kimia, 2021)
Anthocyanins are a group of natural dyes (pigments) that give many colors to plants’ leaves, flowers, and fruits. Anthocyanins are generally acidic and more stable under acidic conditions. One of the plants that contain anthocyanin is the lakum (Cayratia trifolia L.) fruit ripe with a blackish-purple color. This study aimed to determine the best type of acid used to extract anthocyanins from the lakum fruit peel. The extraction process was carried out by maceration method using 96% ethanol solvent acidified with three types of acids, HCl 1%, citric acid 3%, and acetic acid 3%, with an average level of anthocyanin obtained of 283.88, 220.70, and 226.55 mg/L, respectively. This study indicated that the best acid used to extract anthocyanin from the lakum fruit peel with the highest total anthocyanin results was by adding HCl 1%.